HUBUNGAN KARAKTERISTIK KONSUMEN DENGAN KARAKTERISTIK WARUNG LESEHAN DI KOTA SURAKARTA - Edi Wibowo & Setyaningsih Sri Utami (Universitas Slamet Riyadi, 2012)
ABSTRACT This study aims to analyze the relationship between consumer characteristics with the characteristics of stalls to choose eating stall in the city of Surakarta. Consumer characteristics are studied, gender, marital status, age, education, income, and employment of consumers, while the stall characteristics completeness of the product consists of attributes, taste, price, cleanliness, location and service. The population of consumers who eat at food stalls in the city of Surakarta amount is not known for sure. Sample approach with an error probability of 10%, 5% significance level. The number of samples used 100 respondents with accidental sampling technique. Chi Square data analysis techniques and Contingency Coefficient primary consideration of consumers choose to eat at the stall factor is service, backed out of the calculation of the value of the difference Coefficient of Contingency and value Cmak in which the relationship between marital status with service has the smallest difference value (0.412). Factor services that are most closely linked to the consumer's decision to select stalls Surakarta area. Keywords: consumer characteristics, stall characteristics, informed choice to eat at stalls